Grass-livestock balance under the joint influences of climate change, human activities and ecological protection on Tibetan Plateau - Lingyan Yan; Lingqiao Kong; Lijing Wang; Li Zhang; Jinming Hu; Zhiyun Ouyang (Ecological Indicators, 2024)
Grasslands are important terrestrial ecosystems and key sources of primary productivity for livestock on Earth. It is very important to clarify the trend of the balance between grassland and livestock for sustainable development. Focusing on the unique alpine grassland ecosystem that is widely distributed in the Tibetan Plateau (TP), we assessed the grassland carrying capacity (GCC) and overgrazing in 2000, 2010 and 2020 considering grassland productivity, forage utilization of different grassland types, forage loss from diseases and pests and actual grazing intensity. Structural equation modelling was used to analyse the multifactor interactive driving mechanism of changes in GCC and overgrazing. The results showed that 1) From 2000 to 2020, although the total area of grassland decreased slightly, the amounts of edible forage, forage utilization, loss from diseases and pests, and GCC increased by 21.29%, 21.08%, 22.25% and 15.90%, respectively. 2) The overgrazing first intensified and then alleviated from 2000 to 2020 on the TP, but there was a serious grass-livestock imbalance (overgrazing ratio of 119% in 2020), with 80% of its counties being overgrazed in 2020. 3) From 2000 to 2020, climate change and ecological protection created synergistic effects on the grass-livestock balance on the TP. Climate warming and wetting directly raised grassland productivity, and indirectly benefited GCC by promoting grassland restoration and protection. Alleviation of overgrazing by ecological protection shifted from a direct effect to an indirect effect through enhancing the GCC. The contribution of grazing to overgrazing gradually declined as social and economic development relied less on nature over time. Our study quantitatively reveals the dynamic changes in GCC and overgrazing on the TP, and has implications for the sustainable utilization of grasslands in regions such as the TP, where ecosystems are important and fragile and vulnerable to the impact of climate change and human activities.